Respuesta :
Step-by-step explanation:
x+y=-2
x-y=-6
x=-2-y
(-2-y)-y=-6
-2-2y=-6
-2y=-4
y=2
x=-4
Answer: -4 and 2
Step-by-step explanation:
Let the first number be x and the second number be y , then from the question:
[tex]x + y = -2[/tex] ........................ equation 1
[tex]x - y = -6[/tex] ...................... equation 2
solving the of simultaneous linear equation by substitution method , make x the subject of the formula from equation 1 , that is
[tex]x = -2 - y[/tex] ................. equation 3
substitute [tex]x = -2 - y[/tex] into equation 2 , then we have
[tex]-2 - y - y = -6[/tex]
[tex]-2 - 2y = -6[/tex]
[tex]-2 + 6 = 2y[/tex]
[tex]4 = 2y[/tex]
[tex]y = 2[/tex]
substitute [tex]y = 2[/tex] into equation 3 to find the value of x , then we have
[tex]x = -2 - 2[/tex]
[tex]x = -4[/tex]
check:
[tex]x + y = -2[/tex]
[tex]-4 + 2 = -2[/tex]
Also
[tex]x - y = -6[/tex]
-4 - 2 = -6
Therefore: the numbers are -4 and 2